Proposal of a safe and effective study design for CYP3A-mediated drug-drug interactions - Rohr, Brit Silja; Mikus, Gerd (Journal of clinical pharmacology, 2020)
Numerous drug-drug interaction (DDI) trials have to be conducted in healthy volunteers based on current regulatory guidelines. Because the worst-case scenario of strong cytochrome P450 (CYP) inhibitors has to be tested, the results and their validity have to be balanced with the risk to volunteer safety.
First published: 21 May 2020
Gesehen am 15.11.2021